2000
DOI: 10.1007/s004150050601
|View full text |Cite
|
Sign up to set email alerts
|

Typical Friedreich's ataxia without GAA expansions and GAA expansions without typical Friedreich's ataxia

Abstract: We clinically assessed and performed polymerase chain reaction analysis for the GAA trinucleotide repeat expansion in 103 patients from 73 families in Ireland, with a prior clinical diagnosis of Friedreich's ataxia (FA) or an unclassified progressive ataxic syndrome. The patients were classified as "typical" or "atypical" FA according to Harding's mandatory clinical diagnostic criteria. All patients underwent blood glucose analysis, and electrocardiography and echocardiography was performed in 99 and 101 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 25 publications
1
57
0
Order By: Relevance
“…3 He was the offspring of two unrelated Irish parents who had no symptoms of ataxia or neurologic disease.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…3 He was the offspring of two unrelated Irish parents who had no symptoms of ataxia or neurologic disease.…”
Section: Casementioning
confidence: 99%
“…3,5,14 Subject III:1 was estimated to have approximately 954 GAA repeats and subject III:2 was estimated to have 917 GAA repeats on one allele of chromosome 9, but the GAA repeat number on the other allele was normal in both subjects. The diffuse PCR product associated with the GAA expansion in subject III:2 overlapped the expansion in subject III:1 on agarose gel electrophoresis (data not shown).…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…Milbrandt et al (31) determined 63% had scoliosis and 24.5% had hyperkyphos in a series of 77 patients. Previous studies have indicated that foot deformity prevalence was between 55% and 90% (32,33,34,35). In all of our cases, skeletal deformities consisting of one or more of such deformities (pes cavus, kyphoscoliosis, and dome palate) were detected.…”
Section: Discussionmentioning
confidence: 60%
“…Head tremor as a cerebellar sign was once thought to be rare in FA, 2 but recent reports concerning the frequency of various clinical manifestations in different FA phenotypes revealed an unexpectedly high prevalence of head tremor among patients with typical FA. 7 In contrast, head tremor has been described only in exceptional cases of atypical FA. 7 Although involvement of the pyramidal tract, as more commonly seen in patients with late onset forms of FA, was confirmed in our patient by transcranial magnetic stimulation, MRI revealed no atrophy or other abnormality of the spinal cord.…”
mentioning
confidence: 95%
“…7 In contrast, head tremor has been described only in exceptional cases of atypical FA. 7 Although involvement of the pyramidal tract, as more commonly seen in patients with late onset forms of FA, was confirmed in our patient by transcranial magnetic stimulation, MRI revealed no atrophy or other abnormality of the spinal cord. Most patients with typical or atypical FA have been found to have significant cervical cord atrophy 1,8 ; the absence of this finding in our case is unusual.…”
mentioning
confidence: 95%